Can I extract a proof of bounds from an enumeration expression? - proof

Consider this trivial program:
module Study
g : Nat -> Nat -> Nat
g x y = x - y
f : Nat -> List Nat
f x = map (g x) [1, 2 .. x]
It gives an obvious error:
|
4 | g x y = x - y
| ^
When checking right hand side of g with expected type
Nat
When checking argument smaller to function Prelude.Nat.-:
Can't find a value of type
LTE y x
— Saying I should offer some proof that this subtraction is safe to perform.
Surely, in the given context, g is always invoked safely. This follows from the way enumerations behave. How can I extract a proof of that fact so that I can give it to the invocation of g?
I know that I can use isLTE to obtain the proof:
g : Nat -> Nat -> Nat
g x y = case y `isLTE` x of
(Yes prf) => x - y
(No contra) => ?s_2
This is actually the only way I know of, and it seems to me that in a situation such as we have here, where x ≥ y by construction, there should be a way to avoid a superfluous case statement. Is there?

For map (\y = x - y) [1, 2 .. x] there needs to be a proof \y => LTE y x for every element of [1, 2 .. x]. There is Data.List.Quantifiers.All for this: All (\y => LTE y x) [1, 2 .. x].
But constructing and applying this proof is not so straight-forward. You could either build a proof about the range function lteRange : (x : Nat) -> All (\y => LTE y x) (natRange x) or define a function that returns a range and its proof lteRange : (x : Nat) -> (xs : List Nat ** All (\y => LTE y x) xs). For simplicity, I'll show an example with the second type.
import Data.List.Quantifiers
(++) : All p xs -> All p ys -> All p (xs ++ ys)
(++) [] ys = ys
(++) (x :: xs) ys = x :: (xs ++ ys)
lteRange : (x : Nat) -> (xs : List Nat ** All (\y => LTE y x) xs)
lteRange Z = ([] ** [])
lteRange (S k) = let (xs ** ps) = lteRange k in
(xs ++ [S k] ** weakenRange ps ++ [lteRefl])
where
weakenRange : All (\y => LTE y x) xs -> All (\y => LTE y (S x)) xs
weakenRange [] = []
weakenRange (y :: z) = lteSuccRight y :: weakenRange z
Also, map only applies one argument, but (-) needs the proof, too. So with a little helper function …
all_map : (xs : List a) -> All p xs -> (f : (x : a) -> p x -> b) -> List b
all_map [] [] f = []
all_map (x :: xs) (p :: ps) f = f x p :: all_map xs ps f
We can roughly do what you wanted without checking for LTE during the run-time:
f : Nat -> List Nat
f x = let (xs ** prfs) = lteRange x in all_map xs prfs (\y, p => x - y)

Related

foldr for squareOn - Haskell

In my lecture, we had to define the function squareOn such that
with foldr.
The answer was
squareOn :: (Eq a, Num a) => [a] -> a -> a
squareOn = foldr (\x acc y -> if y == x then x*x else acc y) id
I undestand how foldr works, but I'm new at lambda expressions in Haskell. Is acc any type of function from Haskell? It would be nice if someone could explain how squareOn works. :)
This is a sort-of advanced usage of foldr. Normally, we see foldr used as in
fun xs = foldr (\x acc -> something using x and acc) base xs
or equivalently
fun = foldr (\x acc -> something using x and acc) base
which corresponds to the following recursive function:
fun [] = base
fun (x:xs) = something using x and acc
where acc = fun xs
Your case is a special case of this usage, where base, acc, and something using x and acc are functions. That is, we have
fun [] = \y -> base'
fun (x:xs) = \y -> something using x, acc, y
where acc = \y -> fun xs y
Moving back to foldr, we get
fun = foldr (\x acc -> \y -> something using x, acc, y) (\y -> base')
which can also be written as
fun = foldr (\x acc y -> something using x, acc, y) (\y -> base')
where a somehow confusing three-argument function appears to be passed to foldr.
Your specific case,
squareOn = foldr (\x acc y -> if y == x then x*x else acc y) id
corresponds to the explicit recursion:
squareOn [] = id
squareOn (x:xs) = \y -> if y == x then x*x else acc y
where acc = \y -> squareOn xs y
or
squareOn [] y = y
squareOn (x:xs) y = if y == x then x*x else squareOn xs y
which you should be able to understand.
Let's define this function without a lambda.
squareOn :: (Eq a, Num a) => [a] -> a -> a
squareOn = foldr f id
where
f x acc = g
where
g y | x == y = x * x
| otherwise = acc y
Now it's become what foldr usually looks like. It takes a function taking two arguments f and an initial value id.
When you pass [2, 4] to squareOn, it'll be expanded to foldr f id [2, 4], then f 2 (f 4 id) by the definition of foldr.
f 4 id returns a function that takes one argument y which returns 4 * 4 if y is 4, and returns id y otherwise. Let's call this function p.
p y | 4 == y = 4 * 4
| otherwise = id y
Now, f 2 (f 4 id) returns a function that takes one argument y which returns 2 * 2 if y is 2, and returns p y otherwise. When you name it q, it'll be like this.
q y | 2 == y = 2 * 2
| otherwise = p y
So squareOn [2, 4] 3, for example, is equivalent to q 3.
Whoever skipped those explicit arguments just made it unnecessarily harder on yourself to learn this stuff. It's totally superficial. Adding the explicit arguments, as specified by the type signature, gives us
squareOn :: (Eq a, Num a) => [a] -> a -> a
squareOn = foldr (\x acc y -> if y == x then x*x else acc y) id
squareOn xs = foldr (\x acc y -> if y == x then x*x else acc y) id xs
squareOn xs y = foldr (\x acc y -> if y == x then x*x else acc y) id xs y
squareOn xs y = foldr g id xs y where { g x acc y | y == x = x*x
| otherwise = acc y }
squareOn xs y = (case xs of {
[] -> id ;
(x:xs2) -> g x (foldr g id xs2)
}) y where { g x acc y | y == x = x*x
| otherwise = acc y }
Now we can see everything in play here, as opposed to having to keep it all in mind. There is playing chess, and then there's playing blindfold chess, and why play it blindfolded if you can just see?
So now it becomes obvious that passing that y around(*) from call to call unchanged actually has no purpose here, because it is the same y, and it is already in scope:
squareOn xs y = (case xs of {
[] -> y ;
(x:xs2) -> g x (foldr g y xs2)
}) where { g x acc | y == x = x*x
| otherwise = acc }
which simplifies back as just
squareOn xs y = foldr g y xs where { g x acc | y == x = x*x
| otherwise = acc }
{- cf.
squareOn xs y = foldr g id xs y where { g x acc y | y == x = x*x
| otherwise = acc y } -}
And to be pointlessly short and pointfree, like your original code,
squareOn = flip (foldr g) where { g x acc | y == x = x*x
| otherwise = acc }
Or it could be simplified to
squareOn xs y = case xs of {
[] -> y ;
(x:_) | y == x -> x*x ;
(_:xs2) -> squareOn xs2 y }
and further to a worker/wrapper with nested unary worker, whichever is clearer for you.
Passing the unchanged quantity around to have it in scope is only really needed in languages without nested scope, like Prolog.
(*)(so that explanation in full, which you asked for, about how this technique works, is actually in the linked answer).

Functions in Haskell - Understanding

I have the following code which gives out [2,4,6] :
j :: [Int]
j = ((\f x -> map x) (\y -> y + 3) (\z -> 2*z)) [1,2,3]
Why? It seems that just the "z-function" is being used, what happens to the "y-function"?
And how does map work in this particular case?
Let's compute:
((\f x -> map x) (\y -> y + 3) (\z -> 2*z)) [1,2,3]
^^^ f ^^^^^^^ ^^^ x ^^^^^
=
(map x) [1,2,3]
where f = \y -> y +3
x = \z -> 2*z
=
[x 1,x 2,x 3]
where f = \y -> y +3
x = \z -> 2*z
=
[2*1,2*2,2*3]
where f = \y -> y +3
x = \z -> 2*z
=
[2,4,6]
where f = \y -> y +3
x = \z -> 2*z
As we can see, f was taken as an argument, but was never used after that. Consequently \y -> y+3 never affected the final result.
The function map x is the function that applies function x to each element of a list. Note that, above, (map x) [1,2,3] is the same as map x [1,2,3]. Indeed, each function application g x1 x2 x3 x4 can be equivalently written as (((g x1) x2) x3) x4 by left-associating the applications.

Equivalence of two ways of reversing a list

Let's say I have two different functions that reverse a list:
revDumb : List a -> List a
revDumb [] = []
revDumb (x :: xs) = revDumb xs ++ [x]
revOnto : List a -> List a -> List a
revOnto acc [] = acc
revOnto acc (x :: xs) = revOnto (x :: acc) xs
revAcc : List a -> List a
revAcc = revOnto []
and now I want to prove that these functions indeed do the same thing. This is the proof that I came up with:
mutual
lemma1 : (acc, lst : List a) -> revOnto acc lst = revOnto [] lst ++ acc
lemma1 acc [] = Refl
lemma1 lst (y :: ys) = let rec1 = lemma1 (y :: lst) ys
rec2 = lemma2 y ys in
rewrite rec1 in
rewrite rec2 in
rewrite appendAssociative (revOnto [] ys) [y] lst in Refl
lemma2 : (x0 : a) -> (xs : List a) -> revOnto [x0] xs = revOnto [] xs ++ [x0]
lemma2 x0 [] = Refl
lemma2 x0 (x :: xs) = let rec1 = lemma2 x xs
rec2 = lemma1 [x, x0] xs in
rewrite rec1 in
rewrite sym $ appendAssociative (revOnto [] xs) [x] [x0] in rec2
revsEq : (xs : List a) -> revAcc xs = revDumb xs
revsEq [] = Refl
revsEq (x :: xs) = let rec = revsEq xs in
rewrite sym rec in lemma2 x xs
This even type checks and is total (despite the mutual recursion):
*Reverse> :total revsEq
Reverse.revsEq is Total
Note that lemma1 is effectively a stronger version of the lemma2, yet I seemingly need lemma2 since it simplifies the recursive case in lemma1.
The question is: can I do any better? Mutually recursive lemmas with lots of rewrites seem to be overly opaque.
If you do the recursion on a function that keeps revOnto's accumulator explicit, the proof can be quite short:
lemma1 : (acc, xs : List a) -> revOnto acc xs = revDumb xs ++ acc
lemma1 acc [] = Refl
lemma1 acc (y :: xs) =
rewrite lemma1 (y :: acc) xs in
appendAssociative (revDumb xs) [y] acc
revsEq : (xs : List a) -> revAcc xs = revDumb xs
revsEq [] = Refl
revsEq (x :: xs) = lemma1 [x] xs

Idris proof by definition

I can write the function
powApply : Nat -> (a -> a) -> a -> a
powApply Z f = id
powApply (S k) f = f . powApply k f
and prove trivially:
powApplyZero : (f : _) -> (x : _) -> powApp Z f x = x
powApplyZero f x = Refl
So far, so good. Now, I try to generalize this function to work with negative exponents. Of course, an inverse must be provided:
import Data.ZZ
-- Two functions, f and g, with a proof that g is an inverse of f
data Invertible : Type -> Type -> Type where
MkInvertible : (f : a -> b) -> (g : b -> a) ->
((x : _) -> g (f x) = x) -> Invertible a b
powApplyI : ZZ -> Invertible a a -> a -> a
powApplyI (Pos Z) (MkInvertible f g x) = id
powApplyI (Pos (S k)) (MkInvertible f g x) =
f . powApplyI (Pos k) (MkInvertible f g x)
powApplyI (NegS Z) (MkInvertible f g x) = g
powApplyI (NegS (S k)) (MkInvertible f g x) =
g . powApplyI (NegS k) (MkInvertible f g x)
I then try to prove a similar statement:
powApplyIZero : (i : _) -> (x : _) -> powApplyI (Pos Z) i x = x
powApplyIZero i x = ?powApplyIZero_rhs
However, Idris refuses to evaluate the application of powApplyI, leaving the type of ?powApplyIZero_rhs as powApplyI (Pos 0) i x = x (yes, Z is changed to 0). I've tried writing powApplyI in a non-pointsfree style, and defining my own ZZ with the %elim modifier (which I don't understand), but neither of these worked. Why isn't the proof handled by inspecting the first case of powApplyI?
Idris version: 0.9.15.1
Here are some things:
powApplyNI : Nat -> Invertible a a -> a -> a
powApplyNI Z (MkInvertible f g x) = id
powApplyNI (S k) (MkInvertible f g x) = f . powApplyNI k (MkInvertible f g x)
powApplyNIZero : (i : _) -> (x : _) -> powApplyNI 0 i x = x
powApplyNIZero (MkInvertible f g y) x = Refl
powApplyZF : ZZ -> (a -> a) -> a -> a
powApplyZF (Pos Z) f = id
powApplyZF (Pos (S k)) f = f . powApplyZF (Pos k) f
powApplyZF (NegS Z) f = f
powApplyZF (NegS (S k)) f = f . powApplyZF (NegS k) f
powApplyZFZero : (f : _) -> (x : _) -> powApplyZF 0 f x = x
powApplyZFZero f x = ?powApplyZFZero_rhs
The first proof went fine, but ?powApplyZFZero_rhs stubbornly keeps the type powApplyZF (Pos 0) f x = x. Clearly, there's some problem with ZZ (or my use of it).
The problem: powApplyI was not provably total, according to Idris. Idris' totality checker relies on being able to reduce parameters to structurally smaller forms, and with raw ZZs, this doesn't work.
The answer is to delegate the recursion to plain old powApply (which is proven total):
total
powApplyI : ZZ -> a <~ a -> a -> a
powApplyI (Pos k) (MkInvertible f g x) = powApply k f
powApplyI (NegS k) (MkInvertible f g x) = powApply (S k) g
Then, with a case split on i, powApplyIZero is proven trivially.
Thanks to Melvar from the #idris IRC channel.
powApplyI (Pos Z) i x doesn't reduce further because i is not in weak head normal form.
I don't have an Idris compiler, so I rewrote your code in Agda. It's pretty similar:
open import Function
open import Relation.Binary.PropositionalEquality
open import Data.Nat
open import Data.Integer
data Invertible : Set -> Set -> Set where
MkInvertible : {a b : Set} (f : a -> b) -> (g : b -> a) ->
(∀ x -> g (f x) ≡ x) -> Invertible a b
powApplyI : {a : Set} -> ℤ -> Invertible a a -> a -> a
powApplyI ( + 0 ) (MkInvertible f g x) = id
powApplyI ( + suc k ) (MkInvertible f g x) = f ∘ powApplyI ( + k ) (MkInvertible f g x)
powApplyI -[1+ 0 ] (MkInvertible f g x) = g
powApplyI -[1+ suc k ] (MkInvertible f g x) = g ∘ powApplyI -[1+ k ] (MkInvertible f g x)
Now you can define your powApplyIZero as
powApplyIZero : {a : Set} (i : Invertible a a) -> ∀ x -> powApplyI (+ 0) i x ≡ x
powApplyIZero (MkInvertible _ _ _) _ = refl
Pattern-matching on i induces unification and powApplyI (+ 0) i x becomes replaced with powApplyI (+ 0) i (MkInvertible _ _ _), so powApplyI can proceed further.
Or you could write this explicitly:
powApplyIZero : {a : Set} (f : a -> a) (g : a -> a) (p : ∀ x -> g (f x) ≡ x)
-> ∀ x -> powApplyI (+ 0) (MkInvertible f g p) x ≡ x
powApplyIZero _ _ _ _ = refl

What is a function composition algorithm that will work for multiple arguments, such as h(x,y) . f(x) . g(x) = h(f(x),g(x))?

For example, suppose we had the functions double(x) = 2 * x, square(x) = x ^ 2 and sum(x,y) = x + y. What is a function compose such as compose(compose(sum, square), double) = x^2 + 2*x? Notice that I'm asking a function that can be used for functions of any arity. For example, you could compose f(x,y,z) with g(x), h(x), i(x) into f(g(x), h(x), i(x)).
This is a common Haskell idiom, applicative functors:
composed = f <$> g1 <*> g2 <*> ... <*> gn
(A nicer introduction can be found here).
This looks very clean because of automatic partial application, and works like this:
(<*>) f g x = f x (g x)
(<$>) f g x = f (g x) -- same as (.)
For example,
f <$> g <*> h <*> i ==>
(\x -> f (g x)) <*> h <*> i ==>
(\y -> (\x -> f (g x)) y (h y)) <*> i ==>
(\y -> f (g y) (h y)) <*> i ==>
(\z -> (\y -> f (g y) (h y)) z (i z)) ==>
(\z -> f (g z) (h z) (i z)).
Applicative functors are more general, though. They are not an "algorithm", but a concept. You could also do the same on a tree, for example (if properly defined):
(+) <$> (Node (Leaf 1) (Leaf 2)) <*> (Node (Leaf 3) (Leaf 4)) ==>
Node (Leaf 4) (Leaf 6)
But I doubt that applicatives are really usable in most other languages, due to the lack of easy partial application.